2010
DOI: 10.1002/pssc.200983452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Al2O3 incorporation on device performance of HfO2 gate dielectric AlGaN/GaN MIS‐HFETs

Abstract: We report the effects of Al2O3 interfacial layer incorporation on the dc performance of AlGaN/GaN metal‐insulator‐semiconductor field effect transistors (MIS‐HFETs) using HfO2 as the gate dielectric and surface passivation layer. The HfO2/Al2O3 bi‐layer MIS‐HFETs exhibit a larger maximum drain current by ∼8.5%, larger gate voltage swing by ∼6.3%, and smaller gate leakage by 4∼5 times, compared to the HfO2 single layer MIS‐HFETs at room temperature. Furthermore, the HfO2/Al2O3 transistors are observed to have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…La 2 O 3 [137], Pr 2 O 3 [138], Ga 2 O 3 [139], ZrO 2 [140] and HfO 2 [15,139,141] have all been reported, however it is Al 2 O 3 which is the most widely investigated candidate to date [14,18,139,141,142,143,144]. For all of these dielectrics, reduced gate leakage of the MOS-HEMT compared to that of the Schottky HEMT is reported, with additional benefits such as higher drain current, increased immunity to current collapse, increased transconductance and higher breakdown voltage also reported [14,15,18,137,138,139,140,141,142,143,144,145,146]. Once again, ALD shows promising results with one recent report demonstrating reduced trap states at the Al 2 O 3 /AlGaN interface when compared to MOCVD-grown Al 2 O 3 or oxidation of a thin Al surface layer to form Al 2 O 3 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La 2 O 3 [137], Pr 2 O 3 [138], Ga 2 O 3 [139], ZrO 2 [140] and HfO 2 [15,139,141] have all been reported, however it is Al 2 O 3 which is the most widely investigated candidate to date [14,18,139,141,142,143,144]. For all of these dielectrics, reduced gate leakage of the MOS-HEMT compared to that of the Schottky HEMT is reported, with additional benefits such as higher drain current, increased immunity to current collapse, increased transconductance and higher breakdown voltage also reported [14,15,18,137,138,139,140,141,142,143,144,145,146]. Once again, ALD shows promising results with one recent report demonstrating reduced trap states at the Al 2 O 3 /AlGaN interface when compared to MOCVD-grown Al 2 O 3 or oxidation of a thin Al surface layer to form Al 2 O 3 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Once again, ALD shows promising results with one recent report demonstrating reduced trap states at the Al 2 O 3 /AlGaN interface when compared to MOCVD-grown Al 2 O 3 or oxidation of a thin Al surface layer to form Al 2 O 3 [14]. As mentioned in the introduction, some HEMT structures have GaN capping layers on the AlGaN surface [14,142,143] and thus the learning obtained from GaN MOS devices can also be used for the improvement of MOS-HEMT devices. In fact, some reports suggest that the Al 2 O 3 /GaN interface has reduced trap states as compared to the Al 2 O 3 /AlGaN interface [14,142].…”
Section: Discussionmentioning
confidence: 99%
“…g m, max and the GVS of samples A, B and C were determined to be 136/133.1/145.5 ms mm −1 at V DS = 7 V and 2.98/2.71/3.32 V, respectively. Other research works [24,27] showed that the MOS-HEMT with the HfO 2 dielectric has higher g m, max than the device with Al 2 O 3 /HfO 2 -stacked gate dielectrics. In contrast, the observed higher g m, max of samples A and C than sample B is contributed by ( 1 effect.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, HfO 2 dielectric exhibiting low poly-crystallization temperature at about 500 • C [24] and relatively small band-gap may limit their applications as a dielectric material. Hence, some research works utilized the Al 2 O 3 thin film as an interfacial layer between HfO 2 dielectric and a barrier layer by using atomic layer deposition [25,26] and pulse laser deposition [24,27] to further suppress the gate leakage current and improve the interfacial quality.…”
Section: Introductionmentioning
confidence: 99%
“…The studied high-k gate oxides include Al 2 O 3 [4,5], MgO [6], HfO 2 [7], SiO 2 [8], ZrO 2 [9], and TiO 2 [10]. Also, MOS-HFETs with stacked dielectric films have been studied, including using Al 2 O 3 as the surface passivation layer formed by atomic layer deposition (ALD) [11,12] and HfO 2 as the gate contact layer grown by pulse laser deposition (PLD) [13,14]. Our previous work [15] has shown a MOS-HFET with composite Al 2 O 3 /HfO 2 gate dielectrics by using hydrogen peroxide (H 2 O 2 ) oxidation and the RF sputtering technique, respectively.…”
Section: Introductionmentioning
confidence: 99%